Metacarpophalangeal pattern profile in Marfan syndrome and Marfan-like patients - Oliveira Sobrinho, Ruy Pires de; Moretti-Ferreira, Danilo [UNESP]; Contini, Andréia [UNESP]; Norato, Denise Yvonne Janovitz (Wiley, 1997)
Marfan syndrome (MFS) is an autosomal dominant trait due to mutations in the fibrillin gene (FBN1). The MFS expressivity is variable, and its diagnosis relies completely on clinical criteria. Atypical cases and Marfan- like (marfanoid) clinical presentations are commonly found. The metacarpophalangeal pattern profile (MCPP), a radiological method in which the 19 tubular hand bones are assessed, has been used in the diagnosis of various syndromes. To investigate whether the MCPP was adequate to discriminate between MFS and Marfan-like subjects, we studied 38 patients who were referred to our service because they had an MFS diagnosis, diagnostic hypothesis, or differential diagnosis or had arachnodactyly with dolichostenomelia. Two groups were formed: 1) MFS: 21 patients with a mean age of 18.3 (10.8 S.D.) years and 2) Marfan-like syndromes: 16 patients who did not meet the current criteria, with a mean age of 14.6 (4.6 S.D.) years. The MCPP was performed in each case following the classical technique, and a characteristic mean profile was obtained for group I (MFS), with Z scores ranging from 0.69 to 2.73 (1.80 ± 0.50; mean ± S.D.). In group I, three cases had no correlation with the typical MFS pattern. In group II, three cases had an MFS pattern. The correlation with the mean MCPP of MFS permitted the differential diagnosis of MFS and marfanoid syndromes with 86% sensitivity, 81% specificity, and 86% positive and 81% negative predictive values. The results suggest that MCPP can be used effectively as an auxiliary tool in the nosology of these conditions and, because there is no change in MCPP with age, can be helpful in early diagnosis.
Keywords: Diagnosis; Marfan syndrome; Marfanoid; Metacarpophalangeal pattern profile; adolescent; adult; arachnodactyly; child; clinical article; clinical feature; controlled study; differential diagnosis; marfan syndrome; metacarpophalangeal joint; preschool child; priority journal; school child; Adolescent; Marfan Syndrome; Metacarpophalangeal Joint; Middle Aged; Predictive Value of Tests